Standardization of primary processing of fennel (Foeniculum vulgare Mill.) in tribal area of Sirohi (Rajasthan) - D K Sarolia, L Vyas, R L Bhardwaj, U Nadal (Journal of Spices and Aromatic Crops, 2013)
An experiment was conducted in a farmer’s field at Sirohi (Rajasthan) during 2009–10 and 2010–11. Five separate experiments on (i) harvesting time (ii) umbels drying structure (iii) fennel threshing floor (iv) grading stages and (v) packing material of fennel, were laid out in a completely randomized design with four treatments replicated five times. The results revealed that different treatments had significant effect on sensory attributes, geometry and economics of fennel seed quality. The fennel umbels which were harvested at post maturity stage [31-40 days after flower initiation (DAFI)] were superior to rest of the harvesting stages and recorded maximum sensory scores, seed dimensions and highest yield (17.35 q ha-1), maximum market rate (Rs. 150.24 kg-1) and B:C ratio (4.62). Results also showed that drying of fennel umbels in modified locally made structures gave better quality of seed over other structures, giving good market price (Rs. 135.74 kg-1). Threshing on RCC floor was found to be better for maintaining good quality of seed. The grading and packing also improved the quality of seed. The fennel seed which was packed in polyethylene lined gunny bag was found to be better because the quality of seed did not deteriorate in terms of taste, colour, and flavour for longer time. Maximum shelf life of produce along with better quality and higher market price was also obtained in this treatment.